When the Kids Are Not Alright: School Counseling in the Time of COVID-19. (July 2021) - Savitz-Romer, Mandy; Rowan-Kenyon, Heather T.; Nicola, Tara P.; Alexander, Emily; Carroll, Stephanie
The unprecedented arrival of COVID-19 upended the lives of American children with rapid shifts to remote and hybrid schooling and reduced access to school-based support. Growing concerns about threats to students' mental health and decreased numbers of students transitioning to postsecondary education suggest access to school counselors is needed more than ever. Although previous research on school counselors finds they promote positive postsecondary, social emotional, and academic outcomes for students, further studies highlight the organizational constraints, such as an overemphasis on administrative duties and unclear role expectations, that hinder their work. Drawing on survey and focus group data, our mixed methods study documents school counselors' experiences during the COVID-19 crisis, including the opportunities and constraints facing their practice. Findings suggest there should be a concerted effort to reduce the role ambiguity and conflict in counselors' roles so they are better able to meet students' increased needs.